Dirtdobber Blues : A Novel - Vetter, Cyril E. (Book collections on Project MUSE., 2011)
Immensely talented and devastatingly self-destructive, singer/songwriter Charles ôButchö Hornsby lived hard and fast. One of the most versatile artists ever to emerge from South Louisiana, Hornsby touched and frustrated his friends in equal measure. Dirtdobber Blues, a fictionalized account of HornsbyAEs life written by his close friend Cyril Vetter, provides the gritty but engrossing story of this man, his demons, and his art. Much like HornsbyAEs life, Dirtdobber Blues consists of short, fast-paced segments. These vignettes juxtapose musical accomplishments and personal misadventures to paint.